The entrepreneurial development of regions: Exploring the socio-technical transition of Lusatia from a multi-level perspective - Matthias Tomenendal; Hans Rüdiger Lange; Johannes Kirch; Anna Frieda Rosin (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2018)
In the pursuit of strict climate policy targets the German government has decided that several lignite power plants have to be closed down by the year of 2019. One of the most affected regions is the Lusatia mining area in Eastern Germany. Here the question is raised how economic restructuring induced by climate policy can be achieved without bringing havoc on an entire region. We aim to give a first answer by developing a multi-level perspective (MLP) model for supporting regions towards more entrepreneurial activities. Based on different literature streams we suggest a model for strategic niche management towards an entrepreneurial socio-technical regime, which consists of the mid-level in the MLP as the dependent variable and resulting thrusts of strategic niche management as independent variables. The findings are illustrated by the case of Lusatia but are of general nature and can also be applied to other regions. – – Zur Verfolgung klimapolitischer Ziele hat die deutsche Bundesregierung beschlossen, bis zum Jahr 2019 mehrere Braunkohlekraftwerke stillzulegen. Davon betroffen ist auch die Bergbauregion Lausitz im Osten Deutschlands. Unsere Studie zielt darauf ab, ein mehrschichtiges Perspektiven-Modell für die Forcierung unternehmerischer Aktivitäten auf regionaler Ebene zu entwickeln. Auf Basis von einschlägiger Literatur zu unternehmerischen Wachstumsfaktoren und Ökosystemen sowie zu strukturationstheoretisch begründeten Mehrebenen-Modellen der regionalen Entwicklung schlagen wir ein Modell für strategisches Nischenmanagement für ein unternehmerisch geprägtes sozio-technisches Regime vor. Das sozio-technische Regime ist in diesem Modell die abhängige Variable, während die verschiedenen Schwerpunkte des strategischen Nischenmanagements unabhängige Variablen darstellen. Die Ergebnisse, die anhand der Fallstudie der Lausitz illustriert werden, sollen generell auf Regionen anwendbar sein.
Keywords: 330